From partisanship to pluralism: Teaching students how to listen to each other. (December 2017) - Sussman, Daniel
Educators must prepare students to live with the perpetual discomfort of difference. That includes teaching them how to respectfully listen to others' views, especially when those views are in opposition to their own. Borrowing from protocols used in a professional Critical Friends Group, a teacher at a private Quaker school designed a discussion protocol to guide such classroom discussions among teenagers .